Bioética da responsabilidade a partir de Emmanuel Levinas - Longo, Giovan (2023)
The dissertation presented here intends to insert Levinas's thinking in the field of bio-ethics. What the reader has in hand is the result of a theoretical development initiated in the master's thesis and which now has its theoretical field expanded beyond human relations, which is, to bioethical relations. The definition used for bioethics will be that defined by Fritz Jahr and Van Renssaeler Potter, who understand this field of knowledge as including all forms of life. This means that the bioethics described here seeks to extend Levinasian responsibility to non-human animals and plants as well. In order to achieve the proposed objectives, the reflections will be presented in five chapters. The first and second chapters will be dedicated to the con-ceptual definitions referring to the title of the work, which is, what is bioethics and what is responsibility. The others will analyze responsibility for humans, non-human animals and the environment in general. The five chapters are developed from bibliographic reviews that seek to relate classical research and reflections on the subject with some more recent works. As a result, it is intended to show the importance of responsibility for bioethics, highlighting that being responsible for all living beings and for everything that is necessary for the maintenance of life is what constitutes us as humans, in addition to presenting Levinas's thought as being also a bioethical thought.